High multipole transitions in NIXS: valence and hybridization in 4f systems - Gordon, Robert; Haverkort, Maurits W. (epl, 2008)
Momentum-transfer ( q ) dependent non-resonant inelastic X-ray scattering measurements were made at the N 4, 5 edges for several rare-earth compounds. With increasing q , giant dipole resonances diminish, to be replaced by strong multiplet lines at lower energy transfer. These multiplets result from two different orders of multipole scattering and are distinct for systems with simple 4 f 0 and 4 f 1 initial states. A many-body theoretical treatment of the multiplets agrees well with the experimental data on ionic La and Ce phosphate reference compounds. Comparing measurements on CeO 2 and CeRh 3 to the theory and the phosphates indicates sensitivity to hybridization as observed by a broadening of 4 f 0 -related multiplet features. We expect such strong, non-dipole features to be generic for NIXS from f -electron systems.